2019
DOI: 10.1371/journal.pone.0223979
|View full text |Cite
|
Sign up to set email alerts
|

Are hospital nurse staffing practices associated with postoperative cardiac events and death? A systematic review

Abstract: IntroductionPostoperative cardiac events are frequent complications of surgery, and their occurrence could be associated with suboptimal nurse staffing practices, but the existing evidence remains scattered. We systematically reviewed studies linking nurse staffing practices to postoperative cardiac events and two related outcomes, all-cause mortality and failure-to-rescue.MethodsA systematic search of the English/French literature was undertaken in the CINAHL, PsychInfo, and Medline databases. Studies were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 84 publications
1
29
0
Order By: Relevance
“…We found that higher RN understaffing over the first 6 postoperative days was associated with higher odds of POAF occurrence, a finding consistent with that of a growing number of studies that linked RN staffing levels to several surgical outcomes. 18,27,46 Moreover, to the best of our knowledge, the present investigation is the first multisite longitudinal study to measure RN understaffing over the time window during which POAF is most likely to occur. This methodological characteristic, along with our finding of an association of the same magnitude in two administratively distinct UHCs, strengthens the belief that RN understaffing contributes to the incidence of POAF.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We found that higher RN understaffing over the first 6 postoperative days was associated with higher odds of POAF occurrence, a finding consistent with that of a growing number of studies that linked RN staffing levels to several surgical outcomes. 18,27,46 Moreover, to the best of our knowledge, the present investigation is the first multisite longitudinal study to measure RN understaffing over the time window during which POAF is most likely to occur. This methodological characteristic, along with our finding of an association of the same magnitude in two administratively distinct UHCs, strengthens the belief that RN understaffing contributes to the incidence of POAF.…”
Section: Discussionmentioning
confidence: 95%
“…[12][13][14] Among these, an increasing number of studies have suggested that nurse staffing practices in the postoperative period (e.g., using adequate staffing levels, a richer registered nurse (RN) skill mix, higher numbers of RNs educated at the baccalaureate degree level, and more experienced teams of RNs), which are amenable to managerial intervention, are associated with lower rates of surgical mortality and fewer adverse events. [15][16][17][18] Similarly, several recent investigations pointed out that suboptimal nurse staffing practices (e.g., higher RN understaffing and a higher non-RN skill mix) are correlated with worse patient outcomes. [19][20][21] To explain these associations, it has been proposed that nurse staffing practices can improve or weaken nurse surveillance, one of the most important functions of RNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a higher nurse‐to‐bed ratio was associated with improved postoperative outcomes irrespective of hospital Magnet status. There is a well‐recognized body of literature on the relationship of structural measures such as nurse staffing and clinical outcomes 27,28 . In particular, data have demonstrated that higher nurse staffing ratios can directly improve clinical outcomes 21,29 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, hospital reputation, hospital incorporation into integrated delivery systems, and proportion of hospitals' reimbursements in a value-based payment arrangement likely influence provider-payer negotiations and are infrequently included in clinical quality studies. Additionally, there is a wealth of published literature on the correlation between nurse staffing and nurse education and quality outcomes [44][45][46] ; analyzes may benefit from adjustments for these factors.…”
Section: Discussionmentioning
confidence: 99%